Compact design of UHF RFID and NFC antennas for mobile phones. Issue 7 (4th May 2017) - Paredes, Ferran; Cairó, Ignasi; Zuffanelli, Simone; Zamora, Gerard; Bonache, Jordi; Martin, Ferran
Abstract : A small size and low‐profile antenna has been developed in order to provide any mobile phone with ultra‐high frequency (UHF) radiofrequency identification (RFID) reader functionality. For that purpose, a patch antenna topology has been chosen on account of the mobile phone battery, which exhibits an electromagnetic behaviour similar to a metal plane. The low‐profile patch antenna has been designed to operate at the European UHF RFID band. To communicate the mobile phone with the RFID reader module, near‐field communication (NFC) technology has been considered. Thus, an NFC antenna, based on square coils, operating at 13.56 MHz has been also designed. Such antenna has been etched on the opposite side of the patch antenna. Overall dimensions of the prototype are 60 mm × 100 mm, i.e. small enough to fit the dimensions of a mobile phone. As proof of concepts to evaluate the performance of the designed antennas, an UHF RFID reader module and an NFC reader module are tested. The measured read range reaches up to 1 m for some commercial tags.